Antifungal Activity and Potential Mechanism of N-Butylphthalide Alone and in Combination With Fluconazole Against Candida albicans - Gong, Ying; Liu, Weiguo; Huang, Xin; Hao, Lina; Li, Yiman; Sun, Shujuan (Frontiers in Microbiology, 2019)
Candida albicans is a common opportunistic fungal pathogen that may cause nosocomial fungal infections. The resistance of Candida albicans to traditional antifungal drugs has been increasing rapidly in recent years, and it brings a great challenge in clinical treatment. N-butylphthalide is originally extracted from the seed of Apium graveolens and is currently used for the treatment of ischemic stroke in the clinic. This study demonstrated that n-butylphthalide exhibited antifungal activity against Candida albicans with minimum inhibitory concentrations of 128 μg/ml; moreover, n-butylphthalide combined with fluconazole showed synergistic antifungal effects against resistant Candida albicans, resulting in a decrease in the minimum inhibitory concentrations of fluconazole from >512 to 0.25–1 μg/ml. Time-killing curves verified the antifungal activity in dynamic. Besides, n-butylphthalide exhibited anti-biofilm activity against Candida albicans, biofilms preformed <12 h with sessile minimum inhibitory concentrations of 128–256 μg/ml and synergism was observed when n-butylphthalide combined with fluconazole against resistant Candida albicans biofilms preformed <12 h, resulting in a decrease in the sessile minimum inhibitory concentrations of fluconazole from >1,024 to 0.5–8 μg/ml. Furthermore, in vitro antifungal effects of n-butylphthalide were confirmed in vivo. N-butylphthalide prolonged survival rate of larvae infected by Candida albicans, reduced the fungal burden in larvae and caused less damage to larval tissues. Notably, n-butylphthalide inhibited hyphal growth and induced intracellular reactive oxygen species accumulation and a loss in mitochondrial membrane potential, which was a potential antifungal mechanism. Besides, the synergistic effects between n-butylphthalide and fluconazole potentially relied on the mechanism that n-butylphthalide significantly promoted drug uptake, and suppressed drug efflux via down-regulating the drug transporter encoding genes CDR1 and CDR2. These findings demonstrated the antifungal effects and mechanisms of n-butylphthalide against Candida albicans for the first time, which might provide broad prospects for the identification of new potential antifungal targets.